2018
DOI: 10.1139/cjpp-2018-0474
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition effect of phytoestrogen calycosin on TGF-β1-induced hepatic stellate cell activation, proliferation, and migration via estrogen receptor β

Abstract: The present study was designed to investigate the effects of calycosin on hepatic stellate cell (HSC) function and to explore whether the drug exerts its effect through the estrogen receptor. HSC proliferation and migration were measured by MTT assay and transwell chamber assay, respectively. The mRNA and protein expression of α-SMA, COL-I, and ERβ were detected by real-time PCR and Western blotting. The co-localization and expression of α-SMA and ERβ protein were detected by immunofluorescence. All the studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…Soybean isoflavones can alleviate DSS-induced colitis by inhibiting the ERα pathway and downregulating the subsequent activation of the NLRP3 inflammasome ( Gao et al, 2020 ). Phytoestrogen calycosin inhibits the activation, proliferation, and migration of HSCs induced by TGF-β1 via downregulating ERβ ( Deng et al, 2018 ). Comprehensive studies have shown that the mechanism of interaction between estrogen regulators and ligands is complex, and a specific regulator may even have opposite effects under different circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…Soybean isoflavones can alleviate DSS-induced colitis by inhibiting the ERα pathway and downregulating the subsequent activation of the NLRP3 inflammasome ( Gao et al, 2020 ). Phytoestrogen calycosin inhibits the activation, proliferation, and migration of HSCs induced by TGF-β1 via downregulating ERβ ( Deng et al, 2018 ). Comprehensive studies have shown that the mechanism of interaction between estrogen regulators and ligands is complex, and a specific regulator may even have opposite effects under different circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…According to our previous method [16], the migration ability of LX-2 and transfected cells was inspected by 24-well corning transwell chambers (8.0 μm pore size polycarbonate membrane, Corning Costar, USA). Cells were washed with PBS after digestion and resuspended in serum-free DMEM.…”
Section: Cell Migration Assaymentioning
confidence: 99%
“…As phytoestrogens, calycosin inhibits the growth of various tumors through ERβ-mediated signaling pathway. Our previous studies revealed the anti-liver fibrosis effect of calycosin in CCl 4 -induced liver fibrosis in mice and its inhibition effect on the proliferation, migration and activation of HSC-T6 cells [15,16]. JAK/STAT is a key signaling pathway in a variety of cellular activities, including proliferation, differentiation, migration, apoptosis and cell communication, as well as complex biological processes such as inflammation, immune response and cancer development [17].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the PE effects on liver fibrosis by immunomodulation, the O-methylated isoflavone calycosin inhibits the expression of ECM proteins and the proliferation, activation, and migration of HSC induced by TGF-β1. This effect was correlated with calycosin binding and down-regulation of the ERβ5 subtype [195]. Genistein has also been shown to possess hepatoprotective effects in D-GalN-induced fulminant hepatic failure in rats by modulating the NF-κB/MAPK pathways [161] and anti-fibrotic effects in chronic damage by the Smad7-induced inhibition of TGF-β/Smad2/3 [196].…”
Section: Effects Of Female Sex Hormones Oral Contraceptives and mentioning
confidence: 99%